An ankle rehabilitation robot based on 3-RRS spherical parallel mechanism. (August 2017) - Du, Yuting; Li, Ruiqin; Li, Dahai; Bai, Shaoping
This article presents the design modeling of a novel 3-RRS spherical parallel mechanism for ankle rehabilitation applications. The kinematics of the 3-RRS spherical parallel mechanism is established. The degree of freedom of 3-RRS spherical parallel mechanism is calculated using screw theory. The inverse kinematics of 3-RRS spherical parallel mechanism is solved. Eight groups of inverse solutions of 3-RRS spherical parallel mechanism are obtained. A method for forward position analysis is developed with variation and iteration approaches, which is suitable for motor position control. The ankle rehabilitation robot can be widely used in clinical treatment and can also be used at home, hotels, and fitness centers for ankle muscle relaxation.